Understanding the Relationship Between Procurement Performance and E-Procurement Systems Implementation - Aguiar, António Soares (2020)
Information Technology (IT) can help generate a positive contribution, not only to the economic growth but also to a better environment. In this context, our paper aims to analyze the role of electronic procurement systems (EPS) implementation and use on the firm’s green procurement performance. We propose a conceptual model to explain the role of EPS Implementation on procurement performance where the environment component is also included. We hypothesize that: (1) procurement performance is affected by the extent of EPS implementation success; and (2) the relationship between EPS implementation success and procurement performance is moderated by both the power balance (between the focal firm and its suppliers) as well as the extent of internal and external systems integration. Additionally we propose a research methodology to empirically test the conceptual model and associated hypotheses.